Colorectal Cancer Screening Prevalence and Adherence for the Cancer Prevention Project of Philadelphia (CAP3) Participants Who Self-Identify as Black - Blackman, Elizabeth L.; Ragin, Camille; Jones, Resa M. (Frontiers in Oncology, 2021)
Introduction Colorectal cancer is the third leading cause of cancer-related deaths among Black men and women. While colorectal cancer screening (CRCS) reduces mortality, research assessing within race CRCS differences is lacking. This study assessed CRCS prevalence and adherence to national screening recommendations and the association of region of birth with CRCS adherence, within a diverse Black population. Methods Data from age-eligible adults, 50-75 years, (N=357) participating in an ongoing, cross-sectional study, was used to measure CRCS prevalence and adherence and region of birth (e.g., Caribbean-, African-, US-born). Prevalence and adherence were based on contemporaneous US Preventive Services Task Force guidelines. Descriptive statistics were calculated and adjusted prevalence and adherence proportions were calculated by region of birth. Adjusted logistic regression models were performed to assess the association between region of birth and overall CRCS and modality-specific adherence. Results Respondents were 69.5% female, 43.3% married/living with partner, and 38.4% had <$25,000 annual income. Overall, 78.2% reported past CRCS; however, stool test had the lowest prevalence overall (34.6%). Caribbean (95.0%) and African immigrants (90.2%) had higher prevalence of overall CRCS compared to US-born Blacks (59.2%) (p-value <0.001). African immigrants were 5 times more likely to be adherent to overall CRCS compared to US-born Blacks (OR=5.25, 95% CI 1.34–20.6). Immigrants had higher odds of being adherent to colonoscopy (Caribbean OR=6.84, 95% CI 1.49–31.5; African OR=7.14,95% CI 1.27–40.3) compared to US-born Blacks. Conclusions While Caribbean and African immigrants have higher prevalence and adherence of CRCS when compared US-born Blacks, CRCS is still sub-optimal in the Black population. Efforts to increase CRCS, specifically stool testing, within the Black population are warranted, with targeted interventions geared towards US born Blacks.